Development of an integrated duty cycle test method to assess cordwood stove performance. (3rd July 2022) - Morin, Barbara; Ahmadi, Mahdi; Rector, Lisa; Allen, George
ABSTRACT: The US Environmental Protection Agency's (EPA's) New Source Performance Standards (NSPS) for Residential Wood Heaters (RWH) require certification emission testing of prototype appliances. In 2015, EPA revised those standards to further reduce particulate matter emissions from this critical source. However, to achieve that goal, lower emissions measured in certification tests must reflect lower emissions when the appliance is operated in homes. Woodstove certification tests have used either the Federal Reference Method (FRM), a crib wood method, or a cordwood testing method developed by ASTM International that was designated as a broadly applicable Alternative Test Method (ATM) by the EPA until December 2021, when that status was revoked. There is broad agreement that the FRM and ASTM procedures do not simulate typical fueling and operating of wood stoves in the field, raising questions about the efficacy of the current program. Effective emission reduction efforts require robust, accurate, and reproducible test methods. With input from a range of stakeholders, the Northeast States for Coordinated Air Use Management (NESCAUM) developed the Integrated Duty Cycle Test Method for Certification of Wood-Fired Stoves Using Cordwood (IDC), a cordwood testing protocol designed to improve the efficacy of residential wood heater certification testing. That method was approved by EPA as a broadly applicable ATM in 2021. IDC test runs assess appliance performance under a range of operating and fueling conditions representative of typical consumer use patterns. Unlike previous test methods, the IDC protocol requires three replicate runs to assess appliance performance variability. Including variable fueling and operating conditions, along with the requirement for replicates runs, will increase the effectiveness of certification testing and promote the development of improved wood stove technology. This paper reports on experiments conducted to develop and test the IDC method. Implications : Residential wood heating is one of the largest sources of primary particulate matter pollution nationwide. EPA's New Source Performance Standards (NSPS) establish emission limits for this source category and require certification testing of prototype wood appliances to demonstrate compliance with those limits. However, the operating and fueling requirements in NSPS compliance testing protocols do not represent typical conditions in the field. We developed a new testing approach, the Integrated-Duty Cycle (IDC) Test Method, to address the shortcomings of current certification test approaches. The IDC procedure for cordwood stoves, which was approved by EPA as a broadly applicable alternative test method in 2021, assesses appliance operations over various operating and fueling conditions representing typical consumer use patterns in an integrated run and requires three replicate runs to enable the assessment of variability in stove performance. Stoves certified with this method will be equipped to meet the NSPS limits consistently in field operation.